2017
DOI: 10.1163/22125868-12340083
|View full text |Cite
|
Sign up to set email alerts
|

“I’m not an ESL teacher and I’m not trained to do it”

Abstract: This article discusses how teaching faculty in a western Canadian university respond to the growing number of Chinese international students in their classrooms. Interviews (n=21) and survey data (n=60) reveal that professors struggle to communicate academic expectations across language and cultural barriers; develop cross-cultural content; engage students in active learning in the classroom; and provide effective feedback on written work. This in-depth account shows how faculty negotiate demands to both adapt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 31 publications
0
2
0
Order By: Relevance
“…In fear of being disruptive, Chinese ELL students might hold off on asking their instructors for help with questions they have. Studies have suggested that instructors and peers sometimes interpret the 'passiveness' of Chinese international students as signs of disinterest in engaging with others and learning (Jiang & Altinyelken, 2022;Yochim & Servage, 2017). This is despite findings in surveys conducted on the experience of Chinese international students studying abroad that overwhelmingly support the notion that most of these students want to improve their English, make new friends, and gain international experiences (Jiang & Altinyelken, 2022;Xiao, in press).…”
Section: Challenges Faced By International Studentsmentioning
confidence: 99%
“…In fear of being disruptive, Chinese ELL students might hold off on asking their instructors for help with questions they have. Studies have suggested that instructors and peers sometimes interpret the 'passiveness' of Chinese international students as signs of disinterest in engaging with others and learning (Jiang & Altinyelken, 2022;Yochim & Servage, 2017). This is despite findings in surveys conducted on the experience of Chinese international students studying abroad that overwhelmingly support the notion that most of these students want to improve their English, make new friends, and gain international experiences (Jiang & Altinyelken, 2022;Xiao, in press).…”
Section: Challenges Faced By International Studentsmentioning
confidence: 99%
“…Data show that the number of Chinese immigrants moving to the United States has increased in recent decades (Camarota & Zeigler, 2017; Echeverria-Estrada & Batalova, 2020). While becoming familiar with the culture and education system in the adopted land, Chinese families are finding it difficult to sustain Chinese heritage language, culture, and identity (Cui, 2017; Li & Wen, 2015; Yochim & Servage, 2017). Li and Wen (2015) state that “major responsibilities to maintain Asian HL (Heritage Language) have been left to immigrant families and community language schools” (p. 276).…”
Section: Introductionmentioning
confidence: 99%